2017
DOI: 10.1080/02670844.2017.1376847
|View full text |Cite
|
Sign up to set email alerts
|

Properties of nano-SiC/Ni composite coating on diamond surfaces

Abstract: A Ni coating and nano-SiC/Ni composite coating were prepared on diamond surfaces by an electro-co-deposition method. The surface morphology of plated diamond grit and the bonding state between diamond and Fe-matrix bond were characterised by the scanning electron microscopy and energy-dispersive spectroscopy (EDS). The flexural strength and wear resistance performance of the Fe-matrix bonded diamond tool bits were tested. The results showed that the nano-SiC/Ni composite coating possesses a smoother, finer, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…and wherever it is need to high corrosion resistance deposits [8][9][10]. All in all, an inclusion of the ceramic reinforcements into the electrodeposited Ni-based pure and alloy coatings may lead to enhanced tribomechanical and corrosion properties [11][12][13][14][15][16][17][18][19][20]. To date, very few attempts have been made to improve the final properties of Ni-Cu alloy coatings through incorporation of various reinforcing particles.…”
Section: Introductionmentioning
confidence: 99%
“…and wherever it is need to high corrosion resistance deposits [8][9][10]. All in all, an inclusion of the ceramic reinforcements into the electrodeposited Ni-based pure and alloy coatings may lead to enhanced tribomechanical and corrosion properties [11][12][13][14][15][16][17][18][19][20]. To date, very few attempts have been made to improve the final properties of Ni-Cu alloy coatings through incorporation of various reinforcing particles.…”
Section: Introductionmentioning
confidence: 99%
“…Brinksmeier and Glabe [199] demonstrated the potential of TIC and TIN coatings on diamond tools to eliminate chemical wear. Xiao [200] et al showed that the nano-SiC/Ni composite coating can further protect the diamond from graphitization and can result in higher bending strength and wear resistance of the diamond turning tool bit. It can be seen that coatingassisted technology has the potential to improve the machining performance of Fe-based amorphous alloys under SPDT.…”
Section: Other Assisted Machining Methodsmentioning
confidence: 99%
“…In recent years, researchers found that the hardness, corrosion resistance, wear resistance, physical and chemical properties of Ni-W metallic matrix could be improved by the addition of hard ceramic particles (e.g. TiN [5], [6], BN [7,8], WC [9], SiC [10][11][12], Si 3 N 4 [13][14][15], diamond [16], ZrO 2 [17], etc) into the alloy matrix. Several techniques have been used to fabricate Ni-W nanocomposite coating [18], in which the electrodeposition process is a convenient, low-cost, efficient and most widely applied method in various industries [19,20].…”
Section: Introductionmentioning
confidence: 99%